PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DENGAN STRATEGI PEMBELAJARAN BERBASIS MASALAH DI SEKOLAH DASAR - Hayati, Fitri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research aimed to describe improving the student achievement in science learing by using strategy Problem Based Learning at fift grade  elementar in SD Islam Terpadu Cahaya Hati Bukittinggi. The kind of this research is PTK with us kuantitatif and kualitatif research. The result of this research showed that, the student achievement in cycle I was 71,8% with criteria C and this increased to 88,6% with criteria B in cycle II. From the result it can be concluded that strategy Problem Based Learning increasethe students learning achievement in science learning at fift grade in SD Islam Terpadu Cahaya Hati Gulai Bancah Bukittinggi. Kata Kunci: hasil belajar, IPA,  pembelajaran berbasis masalah